Briefly define the Caesar cipher?

The Caesar cipher involves replacing each letter of the alphabet with the letter standing three places down the alphabet .The alphabet is wrapped around, so that the letter following Z is A.
                   C = E (p) = (p + 3) mod (26)
The general Caesar cipher algorithm is
                   C = E (p) = (p + k) mod (26)
         where  k takes the value in the range 1 to 25
The decryption algorithm is
               p = D(C) = (C - k) mod (26)


Feel free to contact the admin for any suggestions and help.